The Role of Metamorphosis in Arabic Children’s Literature - Yahya, Rafi’ Saed (Journal of Humanities & Social Sciences, 2024)
This study investigates the significance of metamorphosis in Arabic children’s literature, contending that it constitutes not only an extraordinary artistic expression but also warrants meticulous examination. The study's significance lies in its endeavor to unearth the implications of incorporating metamorphosis into children's literature. Through a comprehensive analysis of various examples employing symbolic and psychological methodologies, the study aims to shed light on the underlying reasons for the literary fascination with metamorphosis. Is metamorphosis utilized as a thematic element or a narrative technique? Does it serve to augment the fantastical elements within narratives or to invigorate the imagination of both children and adults? Is its primary function to disrupt established storytelling conventions and provoke intellectual inquiry? Furthermore, the study posits that metamorphosis embodies a philosophical endeavor to engage children in existential and cosmic inquiries by encapsulating the inherent conflicts of the universe. Moreover, metamorphosis encapsulates fundamental dichotomies, encompassing concepts such as reward and punishment, love, and hate. These foundational assumptions underpin the study, which aims to explore them across its various sections.In our humble opinion, the study of literary adaptation has not received the requisite attention in scientific research, especially in children's literature. Therefore, we recommend intensifying studies on this subject and paying attention to it, given its multifaceted implications that can shed light on many fields of knowledge.
Keywords: Metamorphosis; Children Literature; Stepmother; transmutations